Legal Protection of Business Judgement Rule for Directors Of State-Owned Enterprises Subsidiaries Causing Losses - Cindy Ludfiyya; Sulistyandari; Maria Mu’ti Wulandari (Judge : Jurnal Hukum, 2025)
The principle of Business Judgement Rule implemented by the Company's Board of Directors to provide legal protection and protect from personal responsibility in making business decisions even if they result in losses, as long as their actions based on good faith and caution (fiduciary duty). This principle regulated in Article 97 paragraph (5) of UUPT, the elements of which are cumulative, if one of the elements in the article is not fulfilled, the Board of Directors is considered guilty (in the sense of intent) or in a state of negligence in carrying out their duties. The research uses a normative legal approach method with an analysis of regulations and jurisprudence related to losses of state-owned enterprise subsidiaries. There is no regulation about the legal status of state-owned enterprise subsidiaries in the event that losses are often qualified as state financial losses. The results of the study that losses of state-owned enterprise subsidiaries cannot always be qualified as state losses if the funds used come from business activities and depend on the theory used. Therefore, legal protection of Business Judgement Rule is needed by the Board of Directors so that they cannot automatically be held criminally responsible for the losses